Effect of Employee Mutation on Job Stress in Gorontalo District Health Office - Pratiwi Biki (Universitas Negeri Gorontalo, 2019)
This study aims to examine and find out about how the influence of employee mutations on employee stress in the Gorontalo District Health Office. The population and sample used in this study were 74 people who were all employees at the Gorontalo District Health Office. Samples were chosen randomly and then the data obtained from the samples were analyzed using simple regression analysis techniques. The results of the analysis show that employee mutations have a significant positive effect on employee work stress. The contribution of the influence given by employee mutations to the ups and downs of employee stress is 34%. While the remaining 66% is influenced by other factors that are not specifically explained in this study. These results indicate that if employee mutations are carried out in accordance with the principles of mutation, then the work stress experienced by employees can be minimized. However, the problem today is how the employee paradigm regarding the mutation itself. Mutations that should have been motivated turned out to be a scourge for employees who entered the list of mutations. Of course this is because the implementation of the mutations that have occurred so far have not referred to the HRM principles, where mutations are carried out in addition to fulfilling the shortage of staff in other units / sections as well as to place employees in accordance with their skills, abilities and fields. Current mutations are political products that are implemented and targeted at individuals who are not considered part of political promises. So, instead of minimizing stress, on the contrary it actually adds to work stress.Keywords: Employee mutation, performance